Language Teacher Education: World Stage Patterns - Robert C. Kleinsasser (University of Muhammadiyah Prof. DR. HAMKA, 2022)
This manuscript developed from a keynote address focusing on patterns in language teacher education. Participants individually and collectively were challenged to consider their role(s) on the world stage of language education through three patterns: context, content, and professional development. They were further encouraged to consider the relationships within and among the three patterns and invited to further sense-make and make meaning during the conference with their presentations and interactions. The keynote was delivered 17 May 2019 at the 36th International Conference on English Teaching and Learning by Taiwan’s English Teaching and Research Association (ETRA) held on the campus of Tunghai University, Taichung, Taiwan.